RUANG NONGKRONG DAN GAYA HIDUP MAHASISWA DI SEKITAR KAMPUS UNIVERSITAS NEGERI MEDAN (STUDI ANTROPOLOGI PENDIDIKAN) - Octavia Br Girsang; Supsiloani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the meaning of hanging out space for students around the State University Campus of Medan, the relationship between the use of hanging space and the formation of student lifestyles, and explain the practice of hanging out in the perspective of educational anthropology. This research is motivated by a change in the function of the hangout space which is no longer just a place to enjoy food and drinks, but develops as a social space that supports interactions, academic activities, and the formation of student lifestyles. This study uses a qualitative research method with a descriptive approach. The research informant is an active student who routinely does hanging out activities at least 2-3 times a week. Data collection techniques are carried out through observation, in-depth interviews, and documentation, while data analysis uses the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that students interpret the hangout room as an alternative learning space, a place to discuss, share experiences, and a means of releasing boredom after undergoing academic activities, meaning that the hangout room has carried out its function as a third place as stated by Ray Oldenburg, which is the third room after home and campus. Thus, it can be concluded that the hangout space has become a social space that acts as a third place that supports the formation of social interactions, the formation of lifestyles, and the non-formal learning process through various activities and experiences that take place outside the classroom.